Resilience, Psychological Well-Being, and Academic Success in Blended Learning: A Cross-Sectional Study among Healthcare Students - Lestari, Retno; Effendy, Nuraeni; Ariningpraja, Rustiana Tasya (Journal of Applied Nursing and Health, 2025)
Background: Students in healthcare are expected to face high clinical and academic stressors that may influence their psychological well-being and academic achievement. Resilience plays a significant role in helping students navigate these challenges while maintaining their well-being. The research examines the relationship between psychological well-being, resilience, and academic achievement among Universitas Brawijaya healthcare students in a blended learning environment. Methods: A cross-sectional research design was employed, and 302 students participated through purposive sampling. Data were collected through the Academic Resilience Scale (ARS-30) and Ryff's Psychological Well-Being Scale, with GPA as an indicator of academic performance. This study was reported in accordance with the STROBE guidelines. Results: A strong positive relationship between resilience and psychological well-being (r = 0.615, p < 0.01), highlighting the focus on resilience as an effective protective factor. There was, nonetheless, no significant correlation between resilience and GPA (r = -0.006, p = 0.913).. Conclusion: Among the psychological well-being factors, environmental mastery, autonomy, and purpose in life contributed significantly to academic resilience. These findings suggest that cultivating psychological well-being, particularly ecological mastery and self-acceptance, can enable resilience in online learning environments.